2014
DOI: 10.1089/rej.2014.1586
|View full text |Cite
|
Sign up to set email alerts
|

A Nested Case-Controlled Comparison of Telomere Length and Psychological Functioning in Breast Cancer Survivors with and without Insomnia Symptoms

Abstract: The ability to achieve sufficient restorative sleep is important in the maintenance of physical and mental health; however, disturbed sleep and insomnia symptoms are a common experience among women with breast cancer. In non-cancer populations, insufficient sleep quantity and quality has been associated with shortened telomere length (TL), a measure of accumulated cellular damage and human aging. This feasibility study compared TL in women previously diagnosed with breast cancer with clinically significant ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Two papers contained two independent data sets as described in the methods section, leading to 38 data sets. These studies are summarized in Table 1; for 5 studies additional data were provided in correspondence with the authors (Garland et al, 2014; Ladwig et al, 2013; Phillips et al, 2013; Shalev et al, 2014; Tyrka et al).…”
Section: Resultsmentioning
confidence: 99%
“…Two papers contained two independent data sets as described in the methods section, leading to 38 data sets. These studies are summarized in Table 1; for 5 studies additional data were provided in correspondence with the authors (Garland et al, 2014; Ladwig et al, 2013; Phillips et al, 2013; Shalev et al, 2014; Tyrka et al).…”
Section: Resultsmentioning
confidence: 99%
“…Participants' mean age varied between 44 and 75 years, and they had stage 0 to stage IV disease. TL was measured in peripheral blood cells in 13 studies (17,19,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), of which eight studies used qPCR and four studies used Southern blot analysis [one study (33) did not report the measurement method]. Twenty studies measured TL in breast tumor tissue (21)(22)(23)(24)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51), of which the majority used FISH (nine studies, five quantitative measures, and four qualitative measures) and Southern blot analysis (five studies); a slot blot method was used in four studies, qPCR in one study, and STELA in one study.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…It is possible that the association of chronological age and insomnia symptoms on shorter LTL begins at an earlier age in adults living with HIV than in the general population, perhaps due to the reduced capacity of response to stress from aggregate effects of multiple comorbid factors, including HIV-related and treatment factors, coinfections, and other common risk factors [15,25,37]. Accumulating evidence indicates that insomnia leads to accelerated biological aging particularly among vulnerable population [12,38]. Prior research showed that frailty, an integrative marker of health and vulnerability, was more common among HIV-infected individuals than the HIV-uninfected [27,39].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the identified significant association between insomnia and shorter LTL in old HIV-infected but not in uninfected individuals, suggest that such adverse effect may begin at an earlier age or is more pronounced in HIV-infected individuals. This may apply to persons with other chronic diseases associated with accelerated aging such as diabetes and cancers [37,38], but requires further investigation. Interventions aimed at improving sleep quality and mental health may help to lessen the adverse effects on cellular aging in HIV-infected individuals particularly those aged 55 or older.…”
Section: Discussionmentioning
confidence: 99%